Outcomes of percutaneous ballon pulmonary valvuloplasty in pulmonary valve stenosis in the pediatric population at Instituto Nacional Cardiovascular-INCOR, Lima, Peru. - Huamán-Benancio, Gian (2022)
Objective. To evaluate the effectiveness of percutaneous balloon valvuloplasty (PBV) in pulmonary valvular stenosis (PS) in pediatrics and its results during follow-up. Methods. Eighty patients with PE who underwent PBV between January 2014 and December 2019 were studied. Demographic, echocardiographic and hemodynamic characteristics of the procedure are detailed through descriptive statistics while parametric and non-parametric statistical tests were used in the follow-up in relation to pulmonary insufficiency and restenosis. Results. The age range was 2 years (interquartile range RIQ 10.5 - 72 months), the predominant sex was male with 56.2%. The transvalvular pulmonary gradient decreased from 61.7 ± 21.2 mmHg to 17 mmHg (RIQ: 11 - 26 mmHg). The immediate BPV success rate was 90%. The median follow-up time was 21 months (RIQ: 5-47.5 months). All patients at follow-up showed some degree of pulmonary insufficiency at each cut-off point, 17% of the cases at the end of follow-up were found to have severe insufficiency. Three cases of long-term restenosis were found (3.8%) and 6 cases (7.5%) were admitted to the operating room for plasty or pulmonary valve replacement. Reported complications reached 10% of cases, of which two patients were admitted to surgery during the procedure for major complications. A significant association was found with severe pulmonary insufficiency at the end of follow-up and the annulus/balloon ratio. Conclusions. BPV is an effective technique in the treatment of pulmonary valve stenosis, with reported complications, but with good results during follow-up.